Quality Management in Polish Biobanking Network—Current Status Before the Implementation of Unified and Harmonized Integrated Quality Management System - Matera-Witkiewicz, Agnieszka; Krupińska, Magdalena; Sitek, Patrycja; Laskowski, Michał; Zagórska, Karolina; Gleńska-Olender, Joanna (Frontiers in Medicine, 2022)
In 2017, Polish Biobanking Network was established in Poland, within BBMRI.pl project titled “Organization of Polish Biobanking Network within the Biobanking and Biomolecular Resources Research Infrastructure BBMRI-ERIC” as a strategic scientific infrastructure concept. One of the key elements of the project was the verification of the current status of QMS in the Polish biobanking institutions and the implementation of common solutions. The main goal was to indicate the current QMS level and determine the starting points for QMS development for each biobank of the Polish Biobanking Network (PBN). Within 3 years, 35 audit visits were performed. The current status and the level of QMS implementation in each biobank were assessed. Five hundred and seventy recommendations were prepared. The data was analyzed using Fischer Exact test to determine whether or not a significant association was observed. Three areas of analysis were covered: (1) BBMRI.pl status, (2) QMS implementation level and (3) private/public party, respectively. The results were discussed within 15 areas. Concluding remarks showed that some differences were observed in the case of subgroups analysis. There is convergence in QMS within the biobanks where Tissue Banks are located. Moreover, some discrepancies between the QMS implementation level in BBMRI.pl Consortium biobanks and PBN biobanks are observed. Nevertheless, the consortium members are obliged to prepare other biobanks willing to enter the PBN as Members/Observers or which already are in the PBN, so that they can meet the requirements of the quality management system that will enable efficient management of biobanking processes in these units. That is why some actions within BBMRI.pl projects are organized to help the whole biobanking community in Poland implement the harmonized solution.